Title and abstract: a good start - Montesinos, Manuel R. (Revista Argentina de Cirugía, 2026)
The substantial volume of publications being currently produced makes it difficult for researchers to read each work, as their time is limited. The selection process is based on the preliminary information provided in the articles: the title and abstract. The title and abstract function as an introduction, encouraging readers to consider reading and citing the research paper in future articles. Consequently, these two components of every scientific article must be written with great care, as all authors want their work to be known and cited.